2017
DOI: 10.1038/srep43409
|View full text |Cite
|
Sign up to set email alerts
|

p53 induces miR199a-3p to suppress SOCS7 for STAT3 activation and renal fibrosis in UUO

Abstract: The role of p53 in renal fibrosis has recently been suggested, however, its function remains controversial and the underlying mechanism is unclear. Here, we show that pharmacological and genetic blockade of p53 attenuated renal interstitial fibrosis, apoptosis, and inflammation in mice with unilateral urethral obstruction (UUO). Interestingly, p53 blockade was associated with the suppression of miR-215-5p, miR-199a-5p&3p, and STAT3. In cultured human kidney tubular epithelial cells (HK-2), TGF-β1 treatment ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 47 publications
1
88
0
1
Order By: Relevance
“…Several miRNAs appear to be pathogenic by promoting inflammation, apoptosis, and fibrosis while other miRNAs may be protective in AKI . Zhang reported that p53 induced miR‐199a‐3p to suppress SOCS7 for STAT3 activation and renal fibrosis in unilateral urethral obstruction . However, miR‐199a‐3p can also regulate p53 expression by targeting CABLES1 in mouse cardiac c‐Kit + cells to promote proliferation and inhibit apoptosis through a negative feedback loop .…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs appear to be pathogenic by promoting inflammation, apoptosis, and fibrosis while other miRNAs may be protective in AKI . Zhang reported that p53 induced miR‐199a‐3p to suppress SOCS7 for STAT3 activation and renal fibrosis in unilateral urethral obstruction . However, miR‐199a‐3p can also regulate p53 expression by targeting CABLES1 in mouse cardiac c‐Kit + cells to promote proliferation and inhibit apoptosis through a negative feedback loop .…”
Section: Discussionmentioning
confidence: 99%
“…Yang and colleagues recently provided a mechanism by which p53 blockade attenuated experimental kidney fibrosis. It appears to signal through the microRNA miR-199a-3p, SOCS7 and STAT3 and the changes in this pathway could be recapitulated in human kidney fibrosis (55•). …”
Section: Promising Therapeutic Strategies From Other Organs Than the Gutmentioning
confidence: 99%
“…The SOCS 1, SOCS2, and SOCS3 have been well characterized, especially SOCS2 suppression leads to osteoarthritis . Further, the suppression of SOCS7 has been reported to activate STAT3 protein which promotes inflammation . The STAT3 has been reported to either activate the immune responses through IL‐6 or suppress the inflammatory responses by activating the antiinflammatory cytokine IL‐10 signaling .…”
Section: Discussionmentioning
confidence: 99%